Multi-Agent-Based Simulation XIII International Workshop, MABS 2012, Valencia, Spain, June 4-8, 2012, Revised Selected Papers - Giardini, Francesca; Amblard, Frédéric (Lecture Notes in Artificial Intelligence,, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 13th International Workshop on Multi-Agent-Based Simulation, MABS 2012, held in Valencia, Spain, in June 2012. The 11 revised full papers presented were carefully selected from 35 submissions. The papers are organized in topical sections on modeling social interactions; cognition and agents behaviors; agents, games and finance; and methodologies and tools.